TRADISI KHATAM QUR’AN DALAM PEMBENTUKAN KARAKTER ANAK DI KECAMATAN TILATANG KABUPATEN AGAM - Lisna Sandora (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2020)
The people of Tilatang Kamang, Agam Regency, West Sumatra have a tradition, namely the tradition of khatam Qur'an children. This tradition is a celebration / gratitude for the success of children in completing their recitation of the Koran (khatam). Usually this activity is held once a year, to be precise during school holidays. This tradition is a tradition that is ingrained in the life of the Tilatang Kamang community. This Quranic tradition of khatam is also found in several other areas in Minangkabau, but each region has its own uniqueness. In Tilatang Kamang this ceremony is enlivened by barracks around the village, the aim is to inform the crowd that there are several children in this area who have successfully finished reading the Qur'an (finished their studies) and can read the Koran properly and correctly. . The ceremony ended with the announcement of the winners of the khatam participants in the recitation of the Qur'an. The research method used is descriptive qualitative with an ethnographic approach. The data collection technique was done by interview and observation, while the data analysis technique used data reduction, reflection, and conclusion. The results of this study illustrate that the Khatam Qur'an ceremony has become a tradition for the Tilatang Kamang community of the Agam Regency for children who have completed their studies and also as one of the requirements for children to continue their education to a higher level.